2000
DOI: 10.1046/j.1365-2222.2000.00672.x
|View full text |Cite
|
Sign up to set email alerts
|

Airway responsiveness to acetaldehyde in patients with asthma: relationship to methacholine responsiveness and peak expiratory flow variation

Abstract: These results indicate that airway hyperresponsiveness to acetaldehyde is a sensitive and specific indicator for separating asthmatic and normal subjects. Airway responsiveness to methacholine or acetaldehyde and PEF variation are not reflecting the same pathophysiological process in the airways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…[37][38][39] The differences between these 2 agents regarding their receptor distribution and ability to induce endothelium-derived vasodilation or constriction of arterial smooth muscles may be involved in the different results obtained in the present study and those of Saitoh et al 24 Because ACh and MCh challenges have been reported to yield similar high levels of sensitivity and specificity for revealing airway hyperresponsiveness, we consider that the differences between these 2 agents did not affect our results. 40 Influences of age, 41 sex, smoking habits, 42 allergic factors, [43][44][45] left ventricular ejection fraction 46 and microvascular angina 47 on airway hyperresponsiveness have been reported. However, no significant differences were observed among the present CSA, CP and control groups with respect to age, sex or coronary risk factors, including smoking and allergic factors.…”
Section: Discussionmentioning
confidence: 99%
“…[37][38][39] The differences between these 2 agents regarding their receptor distribution and ability to induce endothelium-derived vasodilation or constriction of arterial smooth muscles may be involved in the different results obtained in the present study and those of Saitoh et al 24 Because ACh and MCh challenges have been reported to yield similar high levels of sensitivity and specificity for revealing airway hyperresponsiveness, we consider that the differences between these 2 agents did not affect our results. 40 Influences of age, 41 sex, smoking habits, 42 allergic factors, [43][44][45] left ventricular ejection fraction 46 and microvascular angina 47 on airway hyperresponsiveness have been reported. However, no significant differences were observed among the present CSA, CP and control groups with respect to age, sex or coronary risk factors, including smoking and allergic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a cutoff point of 80 mg/ml separating normal from increased bronchial responsiveness to acetaldehyde may appear arbitrary. We have previously found that 92% of the subjects with asthma had a fall in FEV 1 >20% after inhalation of acetaldehyde in concentrations up to 40 mg/ml, while no healthy subject showed significant bronchoconstriction [6]. Furthermore, the challenge procedure with inhaled acetaldehyde was repeatable to within a single doubling dilution in subjects with asthma [24].…”
Section: Discussionmentioning
confidence: 99%
“…Myou et al [4]reported that the airways of 9 asthmatic patients were more responsive to inhaled acetaldehyde than those of 9 healthy subjects. In another study [6], 56 of 61 asthmatic patients had a fall in FEV 1 of more than 20% while no healthy subject showed significant bronchoconstriction after inhaled acetaldehyde. In the present study, increased responsiveness to inhaled acetaldehyde was detected in 13 of the 16 asthmatic patients and, therefore, our results confirm that inhaled acetaldehyde causes bronchoconstriction in most, but not all, patients with asthma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations